2009
DOI: 10.1007/s11090-009-9195-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of the Positive and Negative Electrical Discharges Formed in Liquid Water and Above a Gas–Liquid Surface

Abstract: The physical processes and chemical reactions that take place inside different temperature plasma zones in water are only partially understood. The present study uses the emission spectroscopy and hydrogen peroxide measurements as indicators of the processes that take place on the gas-liquid boundary and inside plasma. Based on the hydrogen peroxide measurements with negative and positive high-voltage polarities as a function of solution conductivity, it was concluded that the main difference between positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 21 publications
3
71
0
Order By: Relevance
“…Water molecules in solution are ionized and activated by collision with these positive ions under the acceleration of cathode drop near the solution surface, followed by formation of primary free radicals, including hydroxyl radical, aqueous electron, hydrogen radical, and so on. [5,[17][18][19] e…”
Section: Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Water molecules in solution are ionized and activated by collision with these positive ions under the acceleration of cathode drop near the solution surface, followed by formation of primary free radicals, including hydroxyl radical, aqueous electron, hydrogen radical, and so on. [5,[17][18][19] e…”
Section: Mechanismsmentioning
confidence: 99%
“…It not only originated from the dissociation of water molecules, but also from the neutralization of aqueous electron by hydrogen ion in acid solution as in our experimental conditions (pH 3.1). [18,61] Littman et al have examined the products of aqueous phase reactions between hydrogen radical and cysteine and found that the cystine was the main product in acid or neutral solution. [62] The formation mechanism was explained satisfactorily by reaction (3).…”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…High voltage (up to 4 kV) was applied between liquid electrolyte cathode and steel anode placed at a distance of 10 mm, h, above the solution surface. The given polarity of a discharge was chosen since it is well known that the discharges with a liquid cathode provide a higher chemical activity [11]. The anode was made from mechanically sharpened stainless steel wire (radius of curvature is *100 lm).…”
Section: Introductionmentioning
confidence: 99%
“…This leads to formation of chemically active species, ultraviolet radiation and shock waves. Lots of active molecular such as hydrogen, oxygen, hydrogen peroxide and active radicals such as hydroxyl radical, hydroperoxyl radical, oxygen radical and hydrogen radical are produced Thagard et al, 2009). Among these active species, hydroxyl radical ( OH) plays an important role in the degradation of organic pollutants in wastewater.…”
Section: Introductionmentioning
confidence: 99%